The relevance of taxpayers' constitutional rights in the light of revenues' powers of search and seizure - Gupta, R (Commercial Law Department, The University of Auckland, 2013)
For the first time in New Zealand, this article investigates the role that the New Zealand Bill of Rights Act 1990 has played in New Zealand taxation case law. To determine this, the article analyses the interaction of the New Zealand Commissioner of Inland Revenue’s powers of search and seizure under ss 16 and 17 of the Tax Administration Act 1994 and s 21 of the Bill of Rights Act 1990. The article demonstrates that the absence of constitutional rights in New Zealand, constitutional entrenchment and the inclusion of s 4 in the Bill of Rights Act 1990 have accounted for differing outcomes in the courts.